Medicine–Food Homology Plants and Bioactive Compounds in Polyendocrine Metabolic Ovarian Syndrome: Multi-Target Mechanisms and Functional Food Potential—A Review - Qiuni Yang; Linzuo Zou; Yuxue Huang; Qingfeng Zhang; Chengyao He; Li Cheng; Chao Zhao (Nutrients, 2026)
Polyendocrine metabolic ovarian syndrome (PMOS), renamed from polycystic ovary syndrome (PCOS) by global consensus in May 2026, is one of the most common endocrine diseases in women of reproductive age, affecting physical and mental health. Growing evidence suggests that medicine–food homology (MFH) plants and their bioactive compounds may help regulate PMOS-related metabolism and reproductive abnormalities through dietary intervention. This review summarizes their reported roles and potential mechanisms. Based on the existing literature, this review presents nine edible plant resources identified under the MFH/dietary-use framework and 21 bioactive constituents or constituent classes, all selected for detailed synthesis from a broader eligible evidence base and with reported PMOS-related bioactivity. Across preclinical studies, these constituents appear to act through convergent, multi-target mechanisms, including anti-inflammatory and antioxidant activities to reduce systemic inflammation, as well as restoring hormone balance, correcting abnormal lipid metabolism, relieving insulin resistance and protecting ovarian function. Importantly, the evidence base remains predominantly preclinical, with few human randomized trials. Key translational barriers include insufficient standardization of preparations and doses, limited oral bioavailability of several constituents, safety and herb–drug interaction concerns, and uncertain formulation feasibility for functional-food applications. By integrating evidence at the plant and compound levels, this review provides a mechanistic rationale—rather than clinical proof—for further investigation of dietary strategies relevant to PMOS and proposes a framework for the development and evaluation of MFH-based functional foods.